2021
DOI: 10.1063/5.0035413
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of negative differential resistance in WS2 homojunction

Abstract: Vertical tunneling junctions showing negative differential resistance (NDR) are realized in WS2 homojunction devices. Mono-/multilayered single crystalline WS2 is grown using chemical vapor deposition. NDR is observed through resonant tunneling in Au/bi-layer WS2/Au and Pt/few-layered WS2/Au tunneling junctions by back-gating at room temperature. While two-dimensional materials have been a central focus of materials research during the past decade, exploiting novel properties in diverse layers of these materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[120] With the emergence of novel materials, RT and resulting multipeak I-V curves have been reported in various structures based on graphene, TMDCs, organic materials, and perovskites. [121][122][123][124][125][126][127][128][129] Most of these works underline the application potential of the demonstrated RT devices in the MVL field, however, since they mainly represent early results, MVL applications are yet to be demonstrated. Several representative works will be briefly introduced in this section.…”
Section: Resonant-tunneling (Rt) Devicesmentioning
confidence: 99%
“…[120] With the emergence of novel materials, RT and resulting multipeak I-V curves have been reported in various structures based on graphene, TMDCs, organic materials, and perovskites. [121][122][123][124][125][126][127][128][129] Most of these works underline the application potential of the demonstrated RT devices in the MVL field, however, since they mainly represent early results, MVL applications are yet to be demonstrated. Several representative works will be briefly introduced in this section.…”
Section: Resonant-tunneling (Rt) Devicesmentioning
confidence: 99%
“…This formed the origin of the Esaki diode. Various methods to realize NDR characteristics such as tunneling devices, Gunn diodes, , single electron transistors, , and molecular devices , have been introduced to date. In particular, NDR studies based on band-to-band tunneling (BTBT) in van der Waals (vdW) heterojunction structures fabricated on two-dimensional (2D) transition metal dichalcogenides (TMDCs) have achieved significant progress due to the atomic-scale thickness and excellent interface quality of the TMDCs. , In general, the NDR performance is mainly determined by the peak-to-valley current ratio (PVCR) of the NDR curve and the current and voltage levels of its peaks and valleys.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits an indirect band gap of ∼1.4 eV in the bulk form and transforms to a direct-band-gap semiconductor (band gap: ∼2.1 eV) in its monolayer limit. , As a result, the effective barrier height in graphene–WS 2 –graphene (GWG) heterostructures is suitable for effective carrier tunneling, and the change in the Fermi level of graphene is comparable to the barrier height, leading to high-performance GWG tunneling transistors with an ON/OFF ratio much higher than FETTs based on graphene–hBN–graphene or graphene–MoTe 2 –graphene heterostructures . A few studies have reported the tunneling devices based on GWG heterostructures, demonstrating high ON/OFF ratio, light emission, and negative differential resistance. ,,, However, a systematic exploration of the electronic properties of GWG tunneling transistors, including the band alignment, the bias-controlled barrier shape, height, and the transition from direct tunneling to Fowler–Nordheim tunneling, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…20 A few studies have reported the tunneling devices based on GWG heterostructures, demonstrating high ON/ OFF ratio, light emission, and negative differential resistance. 20,33,37,38 However, a systematic exploration of the electronic properties of GWG tunneling transistors, including the band alignment, the bias-controlled barrier shape, height, and the transition from direct tunneling to Fowler−Nordheim tunneling, is still lacking.…”
Section: Introductionmentioning
confidence: 99%